The median effective effect-site concentration of remifentanil for minimizing the cardiovascular changes to endotracheal intubation during desflurane anesthesia in pediatric patients - Kim, Eun-Jung (The Korean Society of Anesthesiologists, 2012)
BACKGROUND: Desflurane has the most rapid onset and offset of action among the volatile anesthetic agents used for general anesthesia, but it can cause airway reactivity, tachycardia, and hypertension during induction, especially in pediatric patients. This study was designed to determine a median effective effect-site concentration (EC(50)) of remifentanil to prevent the cardiovascular changes due to tracheal intubation during the 1 minimum alveolar concentration (MAC) desflurane inhalation, which was required to prevent movement in response to a noxious stimulus in 50% of subjects, in pediatric patients. METHODS: Twenty-four pediatric patients between the ages 5-15 years were enrolled in this study. We injected thiopental intravenously, at the same time remifentanil was infused by Target Controlled Infusion (TCI) device. When the target effect-site concentration (Ce) of remifentanil reached a preset level, desflurane was administrated through the facial mask. Then, we assessed the signs of desflurane related airway reactivity and cardiovascular changes for 2 min. The up-and-down criteria was a 20% change in systolic blood pressure (SBP) and a heart rate (HR) between just prior to intubation and 1 min after intubation. The EC(50) of remifentanil was calculated from 8 independent pairs using Dixon's up-and-down method. RESULTS: We studied 24 pediatric patients in range of 1-5 ng/ml of the Ce of remifentanil. No patient showed airway reactivity during the study. The EC(50) of remifentanil to suppress the hemodynamic changes after tracheal intubation during desflurane anesthesia was calculated as 3.4 ± 0.9 ng/ml. CONCLUSIONS: In pediatric anesthesia, the EC(50) of remifentanil to minimize the cardiovascular changes due to tracheal intubation during 1 MAC desflurane anesthesia was 3.4 ± 0.9 ng/ml.